Glypican-1 identifies cancer exosomes and detects early pancreatic cancer - Melo, Sonia A.; Luecke, Linda B.; Kahlert, Christoph; Fernandez, Agustin F.; Gammon, Seth T.; Kaye, Judith; LeBleu, Valerie S.; Mittendorf, Elizabeth A.; Weitz, Juergen; Rahbari, Nuh; Reissfelder, Christoph; Pilarsky, Christian; et al. (Nature (London), 2015)
Exosomes are lipid-bilayer-enclosed extracellular vesicles that contain proteins and nucleic acids. They are secreted by all cells and circulate in the blood. Specific detection and isolation of cancer-cell-derived exosomes in the circulation is currently lacking. Using mass spectrometry analyses, we identify a cell surface proteoglycan, glypican-1 (GPC1), specifically enriched on cancer-cell-derived exosomes. GPC1 + circulating exosomes (crExos) were monitored and isolated using flow cytometry from the serum of patients and mice with cancer. GPC1 + crExos were detected in the serum of patients with pancreatic cancer with absolute specificity and sensitivity, distinguishing healthy subjects and patients with a benign pancreatic disease from patients with early- and late-stage pancreatic cancer. Levels of GPC1 + crExos correlate with tumour burden and the survival of pre- and post-surgical patients. GPC1 + crExos from patients and from mice with spontaneous pancreatic tumours carry specific KRAS mutations, and reliably detect pancreatic intraepithelial lesions in mice despite negative signals by magnetic resonance imaging. GPC1 + crExos may serve as a potential non-invasive diagnostic and screening tool to detect early stages of pancreatic cancer to facilitate possible curative surgical therapy. Glypican-1 identifies cancer exosomes and serves as a biomarker for detection of early pancreatic cancer in patients and mouse models of the disease; the findings may enable early and non-invasive identification, and prevention of malignant cancer. Exoxomes as an early test for cancer Most cells shed so-called extracellular vesicles or exosomes consisting of proteins and nucleic acids enclosed in phospholipid bilayers. Exosomes derived from cancer cells can be isolated from the blood circulation of cancer patients and carry tumour-derived material. Raghu Kalluri and colleagues now identify exosomes containing glypican-1 as a biomarker for early pancreatic cancer, in patients and in mouse models of the disease. These findings may enable non-invasive tests for the early detection of pancreatic cancers.